A SIMPLE TECHNIQUE FOR ISOLATION OF DNA SUITABLE FOR PCR AMPLIFICATION FROM CYTOGENETIC PREPARATIONS - Nunes, M. V.; Demelo, M. B.; Costa, F. F.; Varellagarcia, M. (Soc Brasil Genetica, 1995)
In order to rescue molecular information from chromosome preparations, we describe a rapid procedure to obtain DNA from cytogenetic preparations in microscope slides, stored for one to live years at room temperature. This technique was modified from previously described procedures and the DNA obtained was shown to be suitable for PCR amplification.